Modeling and Analysis of the Turning Performance of an Articulated Tracked Vehicle That Considers the Inter-Unit Coupling Forces - Ningyi Li; Xixia Liu; Hongqian Chen; Yu Zhang (Machines)
The interactions between ground reaction forces and inter-unit coupling forces add complexity to the study of the turning motion of articulated tracked vehicles (ATVs). To accurately analyze the turning performance of an ATV, this study developed a steady-state steering model that captures the effects of load transfer caused by coupling and centrifugal forces. First, based on vehicle kinematics under skidding conditions, formulas that incorporate parameters for the lateral track displacement were derived to calculate the turning radii of the front and rear units. Then, the track traction forces and turning resistance moments were calculated using the shear stress–shear displacement relationship. Finally, a steady-state steering model on firm ground conditions was developed for the vehicle according to mechanical equilibrium conditions, and the model was validated using previously reported data. Analyses of the results revealed that the coupling forces provided the driving moments for the turning motion by the transfer of the centrifugal and ground reaction forces that acted on the front and rear units. During turning, the rear unit had a larger radius than the front unit, and the minimum swept radius of the ATV was dependent upon the radius of the outer track trajectory of the rear unit. Specifically, at a speed of 3.1 m/s and a steering angle of 35°, the vehicle exhibited a minimum outer swept radius of 8.8 m, requiring a turning space equivalent to a 3.1-m-wide road. The required turning space increased as both the steering angle and speed increased.